Alternating Cationic‐Hydrophobic Peptide/Peptoid Hybrids: Influence of Hydrophobicity on Antibacterial Activity and Cell Selectivity. (7th October 2020) - Frederiksen, Nicki; Hansen, Paul R.; Zabicka, Dorota; Tomczak, Magdalena; Urbas, Malgorzata; Domraceva, Ilona; Björkling, Fredrik; Franzyk, Henrik
Abstract: The influence of hydrophobicity on antibacterial activity versus the effect on the viability of mammalian cells for peptide/peptoid hybrids was examined for oligomers based on the cationic Lys‐like peptoid residue combined with each of 28 hydrophobic amino acids in an alternating sequence. Their relative hydrophobicity was correlated to activity against both Gram‐negative and Gram‐positive species, human red blood cells, and HepG2 cells. This identified hydrophobic side chains that confer potent antibacterial activity (e. g., MICs of 2–8 μg/mL against E. coli ) and low toxicity toward mammalian cells (<10 % hemolysis at 400 μg/mL and IC50 >800 μg/mL for HepG2 viability). Most peptidomimetics retained activity against drug‐resistant strains. These findings corroborate the hypothesis that for related peptidomimetics two hydrophobicity thresholds may be identified: i) it should exceed a certain level in order to confer antibacterial activity, and ii) there is an upper limit, beyond which cell selectivity is lost. It is envisioned that once identified for a given subclass of peptide‐like antibacterials such thresholds can guide further optimisation. Abstract : Setting limits : For peptide/peptoid hybrids based on the Lys‐like peptoid residue and each of 28 hydrophobic amino acids in an alternating sequence, two hydrophobicity thresholds were identified: i) it should exceed a certain level to confer antibacterial activity, and ii) there is an upper limit, beyond which cell selectivity is lost.